1996
DOI: 10.1093/brain/119.3.775
|View full text |Cite
|
Sign up to set email alerts
|

Selective loss of myelin-associated glycoprotein from myelin correlates with anti-MAG antibody titre in demyelinating paraproteinaemic polyneuropathy

Abstract: The IgM monoclonal autoantibodies of patients with demyelinating paraproteinaemic polyneuropathy recognize a carbohydrate structure present on both myelin-associated glycoprotein (MAG) and protein zero (P0). These autoantibodies are sufficient to cause the disease but the mechanism of demyelination remains unclear. We have analysed nerve biopsies from eight patients with polyneuropathy and anti-MAG antibodies by quantitative immunohistochemistry and find a concordant pattern of reduced expression of myelin mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Tokuda et al (36) reported binding of IgM antibodies from patients with anti-MAG neuropathy and also mouse monoclonal HNK-1 antibody (20) to derivatives of the glycolipid SGPG containing only the terminal disaccharide SO 3 -3-GlcA(β1-3)Gal. Therefore, we synthesized three different inhibitors, the disaccharides 2, 3, and 4 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Tokuda et al (36) reported binding of IgM antibodies from patients with anti-MAG neuropathy and also mouse monoclonal HNK-1 antibody (20) to derivatives of the glycolipid SGPG containing only the terminal disaccharide SO 3 -3-GlcA(β1-3)Gal. Therefore, we synthesized three different inhibitors, the disaccharides 2, 3, and 4 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The assay was performed according to the manufacturer's protocol. Briefly, test compound, sera from patients or mouse monoclonal anti-HNK-1 IgM antibody (20), and incubation buffer (provided with the kit) were added to a final volume of 50 μL per well. The assay was run in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations